Dynamic IPS²-networks and -operations based on software agents - Meier, H.; Uhlmann, E.; Krug, C. M.; Völker, O.; Geisert, C.; Stelzer, C. (Cranfield University Press, 2009)
This article describes how an IPS² network should be build up by considering the dynamic behavior of the IPS² along its life-cycle. How the network partner could participate and how they allocate their capacities will be also discussed as questions regarding the commissioning by considering the business model. The realization of this concept is based on a multi-agent system. Therefore all service delivery involved IPS² objects like product, network partner and service technicians are represented by software agents. All this will be pointed out by an availability oriented maintenance scenario in the field of micro production.
Organised by: Cranfield University
Keywords: Industrial Product-Service Systems; IPS²; Organization; Multi-Agent System; IPS² Network